Hope in Palliative Care: A Thematic Analysis. Issue 2 (April 2022) - Beng, Tan Seng; Xin, Cheah Ai; Ying, Yeoh Kee; Khuen, Lim Poh; Yee, Anne; Zainuddin, Sheriza Izwa; Chin, Loh Ee; Loong, Lam Chee
Background: Hope is a positive coping mechanism that is important at all stages of illness, more so for palliative care patients.Objective: To explore the experiences of hope of palliative care patients.Methods: A qualitative study was conducted at University of Malaya, Kuala Lumpur, Malaysia. Adult palliative care in-patients were recruited and interviewed with semi structured questions on hope. Transcripts from the interviews were thematically analyzed with qualitative data management software NVIVO.Results: 20 palliative care patients participated in the study. The themes generated from thematic analysis were (1) The notions of hope, (2) The sources and barriers of hope and (3) The contents of hope.Conclusion: Hope is an ever-present source of energy that gives people strength to carry on even in the most adverse situations. Understanding hope from the palliative care perspective may allow healthcare providers to develop strategies to better foster hope in the terminally ill.